Relationship between Delta Rhythm, Seizure Occurrence and Allopregnanolone Hippocampal Levels in Epileptic Rats Exposed to the Rebound Effect - Anna-Maria Costa; Chiara Lucchi; Asiye Malkoç; Cecilia Rustichelli; Giuseppe Biagini (Pharmaceuticals, 2021)
Abrupt withdrawal from antiepileptic drugs is followed by increased occurrence of epileptic seizures, a phenomenon known as the “rebound effect”. By stopping treatment with levetiracetam (LEV 300 mg/kg/day, n = 15; vs. saline, n = 15), we investigated the rebound effect in adult male Sprague-Dawley rats. LEV was continuously administered using osmotic minipumps, 7 weeks after the intraperitoneal administration of kainic acid (15 mg/kg). The effects of LEV were determined by comparing time intervals, treatments, and interactions between these main factors. Seizures were evaluated by video-electrocorticographic recordings and power band spectrum analysis. Furthermore, we assessed endogenous neurosteroid levels by liquid chromatography-electrospray-tandem mass spectrometry. LEV significantly reduced the percentage of rats experiencing seizures, reduced the seizure duration, and altered cerebral levels of neurosteroids. In the first week of LEV discontinuation, seizures increased abruptly up to 700% (p = 0.002, Tukey’s test). The power of delta band in the seizure postictal component was related to the seizure occurrence after LEV withdrawal (r2 = 0.73, p < 0.001). Notably, allopregnanolone hippocampal levels were positively related to the seizure occurrence (r2 = 0.51, p = 0.02) and to the power of delta band (r2 = 0.67, p = 0.004). These findings suggest a role for the seizure postictal component in the rebound effect, which involves an imbalance of hippocampal neurosteroid levels.